2015
DOI: 10.1042/bst20140300
|View full text |Cite
|
Sign up to set email alerts
|

TPC: the NAADP discovery channel?

Abstract: The Ca2+-mobilizing second messenger, NAADP (nicotinic acid adenine dinucleotide phosphate), has been with us for nearly 20 years and yet we still cannot fully agree on the identity of its target Ca2+-release channel. In spite of some recent robust challenges to the idea that two-pore channels (TPCs) represent the elusive "NAADP receptor", evidence continues to accumulate that TPCs are important for NAADP-mediated responses. This article will briefly outline the background and review more recent work pertainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 52 publications
3
49
0
Order By: Relevance
“…NAADP is an extremely potent calcium-releasing agent that promotes calcium release from lysosomal acid calcium stores (Soares et al, 2007; Morgan et al, 2015). NAADP appears to regulate a family of Ca 2+ /Na + channels known as Two pore calcium channels (TPCN1 and 2) (Morgan et al, 2015).…”
Section: Synthesis Of Nad-derived Calcium Second Messengers Cadpr Andmentioning
confidence: 99%
See 2 more Smart Citations
“…NAADP is an extremely potent calcium-releasing agent that promotes calcium release from lysosomal acid calcium stores (Soares et al, 2007; Morgan et al, 2015). NAADP appears to regulate a family of Ca 2+ /Na + channels known as Two pore calcium channels (TPCN1 and 2) (Morgan et al, 2015).…”
Section: Synthesis Of Nad-derived Calcium Second Messengers Cadpr Andmentioning
confidence: 99%
“…NAADP is an extremely potent calcium-releasing agent that promotes calcium release from lysosomal acid calcium stores (Soares et al, 2007; Morgan et al, 2015). NAADP appears to regulate a family of Ca 2+ /Na + channels known as Two pore calcium channels (TPCN1 and 2) (Morgan et al, 2015). These messengers and channels are involved in the regulation of lysosomal function and the process of autophagy (Lu et al, 2013; Morgan et al, 2015).…”
Section: Synthesis Of Nad-derived Calcium Second Messengers Cadpr Andmentioning
confidence: 99%
See 1 more Smart Citation
“…54 The three types of TPC have positively charged voltage-sensing motifs in the S4 transmembrane domain characteristic of the VGICs superfamily, however, it was suggested that only TPC1 and TPC3 are regulated by voltage, 14,63 whereas TPC2 is not. 8,16 TPC1 mRNA transcripts have a molecular weight around 5 kb and those for TPC2 around 3 kb in murine (Table 1). 1,60 However, northern blot and RT-PCR analysis of TPC1 expression in rats and mice confirmed the presence of 2 TPC1 transcripts with different size, being now referred as TPC1A (the first characterized isoform, » 5 kb) and TPC1B (a smaller isoform, » 4 kb).…”
Section: Structurementioning
confidence: 99%
“…4 Still, on the other hand, in 2012 and 2013 2 independent studies refuted that mammalian TPCs were Ca 2C release channels activated by NAADP, probing that they are not Ca 2C but Na C release channels that are not activated by NAADP but by phosphatidylinositol 3,5-bisphosphate (PtdIns(3,5)P2) and inhibited by the mammalian target of rapamycin (mTOR), 5,6 which caused a great commotion regarding TPCs regulation and function among the scientific community. [7][8][9][10] Nowadays, it is accepted that mammalian TPCs not only function as Ca 2C or Na C release channels, but also as H C and K C channels, 11,12 and it has been demonstrated that TPCs can be activated by other signals apart from NAADP and PI (3,5)P2, such as the leucine-rich repeat kinase 2 (LRRK2) 13 or action potentials, 14 and inhibited by Mg 2C concentrations, 15 Ca 2C and Na C ion channels inhibitors, 16,17 or c-Jun N-terminal kinase (JNK) and p38 kinase, 15 apart from mTOR. So that, it seems reasonable that, according to the cellular context, TPCs could be differentially regulated and exert different functions.…”
Section: Introductionmentioning
confidence: 99%